Study of Coelogyne dayana Orchid by in vitro Propagation with Various Concentrations of IAA and BAP - sari, lili indah (Jurnal Sains Pertanian Equator, 2016)
ABSTRACTOrchid is an ornamental plant that can grow well in West Kalimantan Climates. However the population of endemic orchids such as C. dayana has declinedsharply, so the conservation of C. dayana are needed by using plant propagation in vitro. The aims of this study were to evaluate the respons of C. dayana treated with various concentrations of IAA, BAP and its interaction on C. dayana grow in MS medium. The research was conducted at the Biotechnology Laboratory of the Faculty of Agriculture, University of Tanjungpura. This study used a completely randomized design (CRD) with two factors. The first factor was IAA and second factor was BAP, both of these two factor consists of four levels : 0 mg/L, 1 mg/L, 2 mg/L and 3 mg/L. The parameters observed in this study were : the shoots emerging time, number of buds, growing number of leaves, the percentage of plants forming buds, and the percentage of plants forming roots. The result showed that IAA and BAP statistically did not any effect on all variables observed as well as on interaction between them and also IAA dan BAP treated plant showed no better than control plant.